The influence of Burpee on the stability of attention of schoolchildren - Georgiy Polevoy (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To determine the influence of the «Burpee» exercise on the indicators of endurance and stability of attention in children aged 15-16. Methods: the pedagogical experiment was carried out based on a comprehensive school, in the city of Kirov, Russia. The study involved children 15-16 years old in the amount of 52 people. Children from the experimental group additionally performed the "Burpee" exercise. Endurance in children was determined by the test "2000 m", and the stability of attention was determined by the test "Bourdon test". The study used Excel and BioStat to determine Student's t-test. Results: After the pedagogical experiment, the indicators in the control group in the "2000 m" test improved by 1.9% (p > 0.05), and in the "Bourdon test" by 5.9% (p > 0.05). In the experimental group, the performance improved significantly in the "2000 m" test by 9% (p < 0.05) and in the "Bourdon test" by 20% (p < 0.05). Conclusion: if 15-16-year-old schoolchildren perform the "Burpee" exercise in physical education classes, then the indicators of endurance and stability of attention will improve significantly.